Working in the Shadow: Survey Techniques for Measuring and Explaining Undeclared Work - Lilith Burgstaller; Lars P. Feld; Katharina Pfeil (Center for Economic Studies and ifo Institute (CESifo), 2022)
Little is known about the size and determinants of undeclared work. While approaches to measure the shadow economy have been extensively discussed, conventional surveys dominate research on undeclared work. We review and extend this literature by first referring to the most recent survey data on undeclared work in Germany and, second, by discussing four experimental survey techniques as well as their few applications to questions of undeclared work. We argue that the randomized response technique and list experiments would validate and improve prevalence estimates of undeclared work, whereas careful design of information provision experiments and discrete choice experiments would fill the gap on determinants that causally affect decisions to supply and demand undeclared work.
Keywords: H26; E26; O17; D91; 330; undeclared work; experimental survey; survey data